THE INFLUENCE OF DIGITAL MARKETING AND PRODUCT QUALITY ON PURCHASING DECISIONS AT IBL SHOP AND ITS IMPACT ON GENERATION Z CUSTOMER SATISFACTION IN PALU CITY - Hasnianti; Adam, Rosida P.; Ponirin (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
This study aims to determine and analyze the direct and indirect effects of digital marketing and product quality on consumer satisfaction on purchasing decisions at IBL Shop and its impact on generation Z consumer satisfaction in Palu City. Data collection was carried out by distributing questionnaires to consumers who shop at IBL Shop. The sampling technique used a purposive sampling technique using the Roscoe formula with a sample size of 100 respondents. The data analysis technique uses the SEM-Partial Least Square (PLS) method. The results showed that (1) Digital marketing has a positive and significant effect on customer satisfaction at IBL Shop for Generation Z in Palu City (2) Product quality has a positive and significant effect on customer satisfaction at IBL Shop for Generation Z in Palu City (3) Digital marketing has a positive and significant effect on purchasing decisions at IBL Shop for Generation Z in Palu City (4) Product quality has a positive and significant effect on purchasing decisions at IBL Shop for Generation Z in Palu City (4) Product quality has a positive and significant effect on purchasing decisions at IBL Shop for Generation Z in Palu City. (5) Purchasing decisions have a positive and significant effect on customer satisfaction at IBL Shop for Generation Z in Palu City (6) Digital marketing has a positive and significant effect on customer satisfaction through purchasing decisions at IBL Shop for Generation Z in Palu City (7) Product quality has a positive and significant effect on customer satisfaction through purchasing decisions at IBL Shop for Generation Z in Palu City